FINANCING RURAL AND AGRI-FOOD ECONOMY IN THE CONDITIONS OF WORLD CRISIS - Dragos, Ilie (Economics of Agriculture, 2012)
The world economic crisis deprived of liquidities almost all economic sectors, among them also rural and agri-food economy. In these conditions, on the banking system, the state and the warranty funds devolves an essential role in financing rural and agri-food economy which must form the main engine of the national economy. The paper aims at presenting a few financing modalities in the next period which would revive rural and agri-food economy. These financing modalities are the result of cooperation in the financing field between the state, the banks and the warranty funds, in the process of revival of rural and agri-food economy and have at the basis the concepts of lasting crediting and lasting development.